Structure-activity relationship and in silico docking analysis of dicarboximide fungicides on 17β-hydroxysteroid dehydrogenase 1 of human, rat, and pig - Huiqian Chen; Sailing Chen; Yunbing Tang; Yingfen Ying; Shaowei Wang; Yang Zhu; Yiyan Wang; Ren-shan Ge; Ping Duan (Ecotoxicology and Environmental Safety)
Dicarboximide fungicides, including captafol, captan, cyclohexylthiophthalimide, folpet, and procymidone, represent a distinct category of fungicides. 17β-Hydroxysteroid dehydrogenase 1 (17β-HSD1) catalyzes the conversion of estrone to estradiol in mammals. Yet, the impact of these fungicides on 17β-HSD1 activity remains unknown. In this study, we investigated their inhibition using human placental cytosols, rat and pig ovarian cytosols. Our observations revealed that dicarboximide fungicides significantly inhibited human 17β-HSD1 activity. Among them, captan showed the strongest potency, with its IC50 of 1.28 μM, whereas procymidone had an IC50 of 100.71 μM. However, both rat and pig 17β-HSD1 enzymes were less sensitive to the inhibition of these fungicides compared to the human enzyme, with captan displaying an IC50 of 5.65 μM for the rat enzyme and 7.36 μM for the pig enzyme. Correlation analysis indicated a positive correlation between IC50 values and LogP. Docking analysis revealed that these fungicides bound to cofactor or between the steroid and cofactor binding sites. The dithiothreitol treatment demonstrated that the formation of irreversible bonds between dicarboximide fungicides and the cysteine residues played a key role in the inhibition of 17β-HSD1 activity. In conclusion, dicarboximide fungicides inhibit 17β-HSD1 depending on lipophilicity, species, and cysteine residue interactions.